2016
DOI: 10.3390/aerospace3030025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Backward-Facing Step Location on the Aerodynamics of a Morphing Wing

Abstract: Over the last decade, aircraft morphing technology has drawn a lot of attention in the aerospace community, because it is likely to improve the aerodynamic performance and the versatility of aircraft at different flight regimes. With the fast paced advancements in this field, a parallel stream of research is studying different materials and designs to develop reliable morphing skins. A promising candidate for a viable morphing skin is the sliding skin, where two or more rigid surfaces remain in contact and sli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Boroomand and Hosseinverdi [24] and lately Mishriky and Walsh [25]. They have all reported that the aerodynamic outcomes from stepped airfoils are strongly dependent on the baseline airfoil, i.e., it differs from one baseline airfoil to another, a fact that supports the findings of [21] and [22] above.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Boroomand and Hosseinverdi [24] and lately Mishriky and Walsh [25]. They have all reported that the aerodynamic outcomes from stepped airfoils are strongly dependent on the baseline airfoil, i.e., it differs from one baseline airfoil to another, a fact that supports the findings of [21] and [22] above.…”
supporting
confidence: 52%
“…Yet, lift was significantly increased when using the proposed new concepts on the lower surface of the airfoil.For all the newly proposed concepts (2 nd , 3 rd and 4 th generations), as much as 44% increase in the lift-to-drag ratio was achieved regardless of whether the geometry modification was implemented on the upper or lower surface of the airfoil.On the other hand, the conventional stepped airfoils (i.e. the 1 st generation), with a surface modification on the upper surface failed to increase the lift-to-drag ratio, indicating that what worked at low speeds, (gliders and RC airplanes[17][18][19][20][21][22][23][24][25]), might not be suitable for high Mach number and high Reynolds number transonic flows. This was the main reason behind seeking alternative designs to the stepped airfoils.…”
mentioning
confidence: 99%
“…In addition, the turbulence resulted from the aerodynamic discontinuity will either move stall to higher angle of attacks or will produce less aggressive stall than the original airfoil. The use of Fertis' 24 airfoil, which itself was inspired by Kline's ''stepped airfoils'', received a noteworthy attention in the past decades, several computational and experimental studies have been published with encouraging results [25][26][27][28][29] but none of these examined the feasibility of stepped airfoils during transonic conditions, i.e. for controlling the occurrence of shock waves on airfoils.…”
Section: Introductionmentioning
confidence: 99%
“…In all configurations, the step will be located at mid-chord length of the airfoil. For the effect of the step location, the reader can refer to [9]. The main stream fluid is directed at an angle of attack of 2.5° and treated as an ideal gas at 300 K, with its viscosity modeled using the Sutherland three coefficient method.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…From the aerodynamic perspective, the interface between the sliding segments is regarded as backward-facing step incorporated along the chord-wise direction of the airfoil. In a previous study [9], the authors have studied the aerodynamic effect of employing a backward-facing step on the upper surface of a NACA 2412 airfoil. A correlation between the step location the aerodynamic properties was established to show that the step has decreased the lifting capability, increased the drag forces and lowered the critical angle of attack of the stepped airfoil.…”
Section: Introductionmentioning
confidence: 99%